A Critique of the Postmodern Episteme in Selected Contemporary Nigerian Novels (2012)
Western postmodern approach to literary interpretation has, arguably, misinterpreted the cultural and ideological meanings of African literary texts. This has been a critical scholarly problem since the emergence of African literature. Although African literature derives its form and style from Western alternatives, its cultural and ideological contents differ considerably from those of the West. Even though several scholars have variously enunciated the need to jettison Africa‟s reliance on Western modes of interpretation, no extensive research has practically detailed the historical, contextual and futuristic implications of the problem. This study, therefore, investigates the implications and consequences of applying Western critical standards to the interpretation of non-Western societies. It also suggests a possible way out of this problem in African literary research. The study employs the Afrocentric worldview, as propounded by Cheikh Anta Diop and expounded by Molefi Asante. This approach provides the African mind the epistemological polemic to critique postmodern literary theory. The choice of texts is informed by the thematic contiguity of contemporary Nigerian novels like Bandele-Thomas‟s The Sympathetic Undertaker and The Man Who Came in From the Back of Beyond; Okediran‟s Boys at the Border, Dreams Die at Twilight and Tenants of the House; Onwordi‟s Ballad of Rage; Adichie‟s Half of a Yellow Sun; Marinho‟s The Epidemic; Arthur-Worrey‟s The Diaries of Mr. Michael; and Mowah‟s Eating by the Flesh. The method of analysis is a probe into the internal arbitrariness in the texts to reveal the repressed meanings. This deconstructive analytical procedure gives credence to the assertion that the Western literary canon is inadequate to provide a development-driven theoretical standpoint for Nigerian literature. The texts reveal the contradiction in employing the Euro-American postmodern method for the analysis of African literature. The exploration of „traditionally forbidden‟ themes of sex, promiscuity, pornography, homosexuality, moral laxity and corruption in these texts underscores the need for a value conscious African alternative. The innovation of disjointed style undermines the quest for cosmic harmony to the consternation of development-seeking African critics. The hermeneutic differences between Africa and the West are apparent in the different interpretations the two societies ascribe to symbols, totems, motifs, and rituals. The “basic principles” in Africa‟s relative cultural homogeneity are seen in the promotion and sustenance of her history, philosophy, religion, oral and written traditions, languages, ethics, values and cosmogony, tendencies which researchers can advance in their quest for an African theory. However, these “basic principles” cannot be extracted from a Western source. They can only be arrived at through a sustained investigation of African history, culture and tradition. Africa has not yet evolved a fine-tuned “mega theory” which, in evolution and practice, is comparable to the standard now attained by the West. If an Afrocentric theory of reading literature must be formulated, African scholars must be much more grounded in African epistemology. A fuller understanding of the core tenets of African epistemology would show that her system of knowledge is a credible alternative to Western methods of inquiry. This would invariably translate to the reconstruction of knowledge to suit the African need